Artificial intelligence-powered smart vision glasses for the visually impaired - Devi Udayakumar; Sarika Gopalakrishnan; Aparna Raghuram; Arathy Kartha; Arun Kumar Krishnan; Ramkumar Ramamirtham; Ramu Muthangi; Ramakrishna Raju (Indian Journal of Ophthalmology)
Purpose: In India, 4.80 million people are blind, and 4.69 million have severe visual impairment. Globally, the digital era and the advent of artificial intelligence devices offer solutions for daily challenges faced by the visually impaired, but they are often expensive. This study evaluates the acceptance and usability of a cost-effective AI-powered spectacle-mounted assistive device in a multicentric Indian cohort. Methods: Smart vision glass (SVG) is a lightweight tool, mounted on a spectacle frame with braille-coded keys and a real-time voice interface for guiding the visually impaired, and is connected to a smartphone Android App. The four major functions of the device are as follows: “Things Around You,” “Reading,” “Walking Assistance,” and “Face Recognition.” Ninety participants were recruited from five vision rehabilitation centers across India, and feedback was collected after a month’s usage. Results: The mean age of the participants was 23.5 years (range: 6 to 56 years) with 58.9% male; 51% from rural areas; and 64.4% students. As per the World Health Organization (WHO) classification, 90% of the participants were blind (best corrected visual acuity in better eye less than 3/60). A total of 100% of the participants were able to access all the functions of the SVG. Participants reported a positive experience with “Reading” (72.9%), “Things Around You” (44.7%), “Face Recognition” (36.5%), and “Walking Assistance” (22.4%). About 2/3rd of the participants utilized the device for an hour or more per day. Conclusion: SVG is a promising cost-effective device for the blind and severe visually impaired in aiding their day-to-day challenges and becoming self-reliant.